Falcondance - Atwater-Rhodes, Amelia (New York : Delacorte Press, 2005)
As the peaceful coexistence of the avian and serpiente realms becomes increasingly precarious, nineteen-year-old Nicias, heir to the ancient and powerful falcon realm, learns some lessons about the past that will shape the future of their shared world.
12 & up.
870
Accelerated Reader AR
Keywords: Falcons -- Fiction; Self-realization -- Fiction; Birds -- Fiction; Snakes -- Fiction; Fantasy